Net radiation distribution in India (MAUSAM, 1985)
Net radiation at Waltair is estimated from easily available meteorological data using several inter-dependent formulae. The computed values agreed well with the measured values. The best of the equations is then used to estimate the net radiation over vegetation in different parts of the country. Net radiation distribution over the country in different months of the year is discussed.